2022
DOI: 10.3389/fneur.2022.1024743
|View full text |Cite
|
Sign up to set email alerts
|

Laryngopharyngeal reflux as a potential cause of Eustachian tube dysfunction in patients with otitis media with effusion

Abstract: ObjectiveTo explore the association between laryngopharyngeal reflux disease (LPRD)-related symptoms and the Eustachian tube (ET) function in adult patients with otitis media with effusion (OME).Materials and methodsA total of 105 adult patients with OME were retrospectively studied. All these patients had undergone tubomanometry (TMM) test for the affected ears before treatments. The LPRD-related symptoms were all assessed by the Reflux Symptom Index (RSI) scale.ResultsAmong the 105 included patients, the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Laryngoscopy also revealed that the patient had ETD associated with LPR. These findings emphasize the significance of looking into LPR as a possible cause of ETD and its symptoms [13][14][15]. On the other hand, ETD can cause negative or positive pressure in the middle ear, which makes the autonomic nervous system let acid back up into the throat.…”
Section: Discussionmentioning
confidence: 72%
“…Laryngoscopy also revealed that the patient had ETD associated with LPR. These findings emphasize the significance of looking into LPR as a possible cause of ETD and its symptoms [13][14][15]. On the other hand, ETD can cause negative or positive pressure in the middle ear, which makes the autonomic nervous system let acid back up into the throat.…”
Section: Discussionmentioning
confidence: 72%
“…A study of individuals with BMS identified that 94% of them had LPR, and that their BMS significantly improved following LPR treatment . Zhen et al (2022) describe otitis media with effusion (OME) as fluid in the middle ear. Symptoms include earache, ear fullness, hearing loss, and tinnitus.…”
Section: Consequences and Associated Conditionsmentioning
confidence: 99%
“…In clinical practice, oropharyngeal pH monitoring could be an interesting diagnostic approach for the detection of nasopharyngeal reflux events. Indeed, the gastric content of pharyngeal reflux events may reach the sinonasal mucosa, Eustachian tube, and tears, which is associated with dry eyes, otitis media, Eustachian tube dysfunction, dry nasal mucosa, nasal crusts, or mulberry turbinate (Figure 4) [87][88][89][90]. Because there is no nasopharyngealhypopharyngeal-esophageal impedance-pH monitoring probe available in the market, the placement of oropharyngeal-pH monitoring sensors in the nasopharynx may be used to confirm nasopharyngeal reflux disease in such patients [91].…”
Section: Oropharyngeal and Nasopharyngeal Ph Monitoringmentioning
confidence: 99%